On Certain Dysfunctions in the Management of Independent Public Health Care Units - Klich, Jacek (Journal of Public Governance, 2009)
The paper focuses on certain determinants of the health care reform carried out in Poland between 1999 and 2004 related to independent public health care units. It is argued that in the Polish health care sector, the basic conditions for effective execution of property rights have not yet been created. This is the primary reason why one may observe considerable dysfunctions in the process of managing independent public health care units. These dysfunctions originate from serious limitations in classic ius utendi at abutendi, ius fruendi and ius disponendi ownership rights implementation. The paper identifies basic dysfunctions at both regulatory and functional levels. Among them, a structural asymmetry between the payer and providers, as well as inefficient governance control over independent public health care units are presented. The paper shows that all these lead to increasing transaction costs and petrify inefficiencies in the health care system.